Matemática financeira no ensino médio: educando para a vida - Matias, Roberto Fernandes (2018)
This paper aims to present concepts and proposals of activities involving education and financial mathematics. It was sought to work with financial education because it is a subject that little or almost never is contemplated in high school and of great relevance in the student's life, which in turn, to be well structured, requires concepts of financial mathematics. As background, we used documents that present teaching proposals on the subject, demonstrating the importance of working in schools. Thus, the main objective of the work is to propose situations that can be developed in the classroom and that lead the student to reflect on the decision making about the management of their financial resources. However, when working on financial mathematics, it was sought to develop it within the rigor required by mathematics, with definitions, propositions and demonstrations.